Primary Healthcare reconditioning to face the COVID-19 pandemic, and perception by professionals of the measures implemented in a Brazilian district - Nascimento, Carolina Carvalho Menez Pinto [UNESP]; Moimaz, Suzely Adas Saliba [UNESP]; Saliba, Tânia Adas [UNESP]; Garbin, Cléa Adas Saliba [UNESP]; Saliba, Nemre Adas [UNESP] (Grupo Paradigma, 2023)
Objective: to describe the Primary Care (PC) scenario regarding reconditioning, equipment and organization of services in order to face the pandemic and to measure the perception by professionals regarding these adaptations. Method: a research with mixed method in a city of the San Pablo state (Brazil). In the quantitative stage, a descriptive cross-sectional study was conducted in 222 PC professionals; the adapted Risk assessment and management of exposure of health care workers in the context of COVID-19 questionnaire by the World Health Organization was implemented. This was followed by the qualitative approach, which consisted in field observation in four PC units. Results: out of the total, 86.94% (n= 193) mentioned that there was an assessment of the signs and symptoms of the users before consultation; 63.96% (n=142) stated that a daily cleaning routine was followed in the waiting room; 92.34% (n= 205) claimed that there were methods available for hand hygiene; 77.48% (n= 172) said that appointments were scheduled in order to maintain physical distancing; 80.12% (n= 178) had not conducted any reconditioning work, and 45.95% (n=102) provided educational materials to users. Conclusions: during field observation, some assessments for signs and symptoms in users were detected; no cleaning actions were observed in the units, it was perceived that there was not enough alcohol gel in the dispenser, there were no marks on the floor to keep distancing, there was a lack of educational materials, and it was not verified that any reconditioning work had been conducted. During data integration, there was convergence regarding physical structure and unit reconditioning.
Reacondicionamiento de la Atención Primaria de Salud para enfrentar la pandemia COVID-19 y percepción de los profesionales sobre las medidas emprendidas en un municipio brasileño
Keywords: COVID-19; health services; healthprofessionals; Pandemic; primary health care